Crecimiento y desarrollo de Caryocar glabrum "almendra" utilizando diferentes dosis de NPK en la parcela 15 del CIEFOR - Puerto Almendra, Loreto - Perú. 2021 - Loja Aleman, Eva Maria (2022)
The study was carried out in Parcel No. 15 of 1 ha in Ciefor - Puerto Almendras, evaluating 200 Caryocar glabrum plants, planted every 5 meters and in 10 strips. The greatest increase in diameter was presented by treatment E (80% NPK dose) with a value of 0.39 mm between the first and last evaluation. There is a difference between the averages of the increase in diameter of the plants, where treatment E (80% of NPK dose) presents the highest average with 33.95 mm. The greatest increase in height was presented by treatment D (60% of NPK dose) with a value of 21.73 cm between the first and last evaluation. The results of the non-parametric Kruskal Wallis test for the comparison of height increase and the treatments indicate that there is a difference between the averages, the treatment E showing the highest value with 27.73 cm. The highest survival was presented by treatment D with 136 live plants. Also, 149 dead plants in the Caryocar glabrum plantation; Treatment D (60% NPK dose) presented a total of 10 plants with good quality, followed by treatment C (40% NPK dose) with 06 plants with good quality. At a general level in the experiment, the Regular quality (Treatment B, C and E) was recorded for the Caryocar glabrum seedlings at the end of the study.